Animacy and animate imagery improve retention in the method of loci among novice users. - Blunt, Janell R.; VanArsdall, Joshua E. (Memory & Cognition, 2021)
Recently, researchers have identified word animacy as a strong predictor of recall. In contrast, the method of loci is an ancient mnemonic technique which takes advantage of highly structured encoding and recall processes alongside a strong imagery component to create easily remembered "memory palaces." The present experiments examine the combined effectiveness of these techniques: Experiment 1 (N = 154) demonstrates that the method of loci and word animacy have additive effects, while Experiment 2 (N = 200) demonstrates that the additive effect of animacy is likely related to both the animate nature of words themselves and animate imagery associated with them. These results have implications for hypotheses about the proximate mechanism of animacy effects (ruling out temporal order and imagery as explanations), implications regarding the nature of animacy (as being both static and dynamic), and practical implications for memory athletes and educational settings alike: The method of loci and use of animate imagery can be taught easily, and they produce high levels of recall.